A New Proposal of Cellulosic Ethanol to Boost Sugarcane Biorefineries: Techno-Economic Evaluation - Juliana Q. Albarelli; Adriano V. Ensinas; Maria A. Silva (International Journal of Chemical Engineering)
Commercial simulator Aspen Plus was used to simulate a biorefinery producing ethanol from sugarcane juice and second generation ethanol production using bagasse fine fraction composed of parenchyma cells (P-fraction). Liquid hot water and steam explosion pretreatment technologies were evaluated. The processes were thermal and water integrated and compared to a biorefinery producing ethanol from juice and sugarcane bagasse. The results indicated that after thermal and water integration, the evaluated processes were self-sufficient in energy demand, being able to sell the surplus electricity to the grid, and presented water intake inside the environmental limit for São Paulo State, Brazil. The processes that evaluated the use of the bagasse fine fraction presented higher economic results compared with the use of the entire bagasse. Even though, due to the high enzyme costs, the payback calculated for the biorefineries were higher than 8 years for all cases that considered second generation ethanol and the net present value for the investment was negative. The reduction on the enzyme load, in a way that the conversion rates could be maintained, is the limiting factor to make second generation ethanol competitive with the most immediate uses of bagasse: fuel for the cogeneration system to surplus electricity production.